Indiana Jones and the temple of doom [videorecording (Blu-Ray)] - Spielberg, Steven, 1946-; Ford, Harrison, 1942-; Capshaw, Kate; Quan, Jonathan Ke, 1971- (Paramount, 2013)
Indiana Jones sets out to find the famous Ankara Stone in order to save hundreds of children who have been enslaved by a mysterious Indian cult.